The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1970
DOI: 10.5424/sjar/20110904-470-10
|View full text |Cite
|
Sign up to set email alerts
|

Main landscape metrics affecting abundance and diversity of game species in a semi-arid agroecosystem in the Mediterranean region

Abstract: Hunting bags provide important information for conservation measures and wildlife management. This study is to assess relationships between landscape structure and game species. The community parameters (abundance, richness and diversity) and landscape/land use indices have been related, using GIS and statistical analysis, in the South-East of Spain (Marina Baja, Alicante). Game species richness (S) is determined by the presence of fruit groves (p = 0.001, R = 0.714) and landscape shape. The total density of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A comparison with nest densities reported in Algerian populations (Table 2) further demonstrates the importance of Moroccan irrigated areas as a high-density nesting zone for African Turtle-doves. In studying the main landscape metrics affecting abundance of game species in a semi-arid agroecosystem in the Mediterranean region, Belda et al (2011) have also reported the great abundance of Turtle-doves in irrigated fruit orchards in Europe.…”
Section: Estimation Of Population Size: the Case Of The Tadla Irrigatmentioning
confidence: 99%
“…A comparison with nest densities reported in Algerian populations (Table 2) further demonstrates the importance of Moroccan irrigated areas as a high-density nesting zone for African Turtle-doves. In studying the main landscape metrics affecting abundance of game species in a semi-arid agroecosystem in the Mediterranean region, Belda et al (2011) have also reported the great abundance of Turtle-doves in irrigated fruit orchards in Europe.…”
Section: Estimation Of Population Size: the Case Of The Tadla Irrigatmentioning
confidence: 99%
“…Previous studies indicate that rabbits are influenced by landscape shape index (p = 0.015; R = 0.580) and are distributed irregularly over the surface of the region (Belda et al 2011). This species prefer ecotone areas, where they can find the basic requirements for their survival in a small space.…”
Section: Discussionmentioning
confidence: 97%
“…The greatest presence of rabbits in the census is found in the irrigated lands, dominated by citrus and medlar orchards, despite being a matrix that only occupies 15.09% of the total surface area (Belda et al 2011). In contrast, drip irrigation enables fresh grass to be present all year round; therefore, the rabbits have more food of a better quality here than in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations